Benefits of Plant Nutrition: A Review - Zeki, Dr. Huda Farooq (International Journal of Psychosocial Rehabilitation, 2020)
There are many research and studies, which indicate the importance of a vegetarian and natural diet, due to the importance of the system in maintaining a healthy body content differed one, refraining from eating foods consisting of animal sources such as meat, fish, eggs and milk, and resorting to nature as a source of food. As natural or vegetarian nutrition is considered the best way for some people to have a healthy body, but others support refraining from eating processed foods such as white flour or refined sugar. There are vegans, who do not eat foods that are not organically grown. A small number of people eat only raw food and stay away from cooked food. And we call them natural or vegan contain almost all of the mineral and organic nutrients established as essential for human nutrition, as well as a number of unique organic phytochemicals that have been linked to the promotion of good health because the concentrations of many of these dietary constituents are often low in edible plant sources.